آليات الاستدلال والتحقيق في جرائم الإنترنت: دراسة تحليلية مقارنة في ضوء التشريع الإماراتي والتحديات العملية: Mechanisms of Evidence Collection and Investigation in Cybercrime: An Analytical Comparative Study in Light of UAE Legislation and Practical Challenges - Algabri, Zayed Ali Nasser; Yusof, Arif Fahmi MD; Ahmad, Nisar Mohammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يركز البحث على جرائم الإنترنت أو الجرائم المعلوماتية من حيث طبيعتها، تعريفها الفقهي والقضائي، وخصائص شبكة الإنترنت التي تجعلها بيئة مثالية لارتكاب هذه الجرائم. يوضح البحث أن الإنترنت رغم فوائده الكبيرة في التواصل والمعرفة، يعتبر سلاحًا ذا حدين بسبب استغلاله من قبل محترفي التقنية لارتكاب جرائم معقدة عابرة للحدود. تناول البحث دور سلطات التحقيق والشرطة في دولة الإمارات العربية المتحدة في جمع الأدلة الرقمية لمواجهة هذه الجرائم، رغم صعوبة إثباتها باستخدام الطرق التقليدية. كما استعرض آليات الضبط والتفتيش، مع التركيز على الخلافات المتعلقة بالطبيعة المادية للبيانات الإلكترونية كأدلة قضائية، مؤكداً أهمية جمع أدلة رقمية مشروعة وفق القانون والدستور. وأشار البحث إلى عدة تحديات تواجه السلطات، منها احتراف الجناة وقدرتهم على إخفاء الأدلة، التشفير العالي للمعلومات، غياب التعاون الدولي الكافي، نقص التشريعات الملائمة، وضعف وعي المستخدمين بكيفية حماية بياناتهم. كما عرض نماذج قضائية من محاكم الإمارات توضح تطبيق التشريعات الحديثة على وقائع متعددة. خلص البحث إلى غياب تعريف دقيق وواضح للجريمة المعلوماتية في التشريع الإماراتي، وضرورة تطوير التعاون الدولي لمكافحة هذه الجرائم. وأوصى بإعداد كوادر شرطية وقضائية متخصصة، وضع تعريف قانوني واضح، زيادة توعية المجتمع بمخاطر الإنترنت وسبل الحماية، والاستعانة بخبراء تقنيين لدعم التحقيقات. كما أبرز البحث جهود الإمارات في تحديث التشريعات وتنظيم تدريبات تخصصية ومؤتمرات علمية لمواكبة التطورات التقنية والحفاظ على الأمن المعلوماتي والمجتمعي، مؤكداً ضرورة استمرار تطوير المنظومة القانونية والتدريبية لمواجهة تحديات الجرائم المعلوماتية. ABSTRACT The research focuses on cybercrimes or information crimes in terms of their nature, their jurisprudential and judicial definitions, and the characteristics of the internet that make it an ideal environment for committing these crimes. The research demonstrates that the internet, despite its significant benefits in communication and knowledge, is a double-edged sword due to its exploitation by technology professionals to commit complex, cross-border crimes. The research addresses the role of investigative authorities and police in the United Arab Emirates in collecting digital evidence to combat these crimes, despite the difficulty of proving them using traditional methods. It also reviews the mechanisms of seizure and inspection, focusing on disputes related to the physical nature of electronic data as judicial evidence, emphasizing the importance of collecting legitimate digital evidence in accordance with the law and the constitution. The research points to several challenges facing authorities, including the professionalism of perpetrators and their ability to conceal evidence, high-level encryption of information, the lack of adequate international cooperation, the lack of appropriate legislation, and the lack of awareness among users about how to protect their data. It also presents judicial models from UAE courts that illustrate the application of modern legislation to various incidents. The research concludes that there is a lack of a precise and clear definition of information crime in UAE legislation and the need to develop international cooperation to combat these crimes. It recommended the development of specialized police and judicial personnel, the establishment of a clear legal definition, increased community awareness of the dangers of the internet and ways to protect it, and the use of technical experts to support investigations. The study also highlighted the UAE's efforts to update legislation and organize specialized training and scientific conferences to keep pace with technological developments and maintain information and community security, emphasizing the need to continue developing the legal and training system to address the challenges of cybercrimes.